(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Children develop different types of emotional bonds to those who care for them. This fact is pertinent here because attachment styles take the form of disparate, relatively stable patterns of emotionality that influence relationships, reactions to stress or loss, and other emotional dilemmas in life. Different attachment styles create different personalities for an adult. Due to this reason, recognizing our attachment pattern can help us understand the strengths and weaknesses of our personality. This study aims to identify the relationship between adult attachment, personality, and emotional intelligence among trainee counselors at Universiti Malaysia Sarawak (UNIMAS). This research adopted a correlational research design. The sample consists of 106 respondents from year 3 and year 4 trainee counselors at Universiti Malaysia Sarawak. The study consists of three main variables, which are attachment dimension, Big Five Personality, and emotional intelligence. In this study, the questionnaires used were Experience in Close Relationship (ECR), Big Five Personality, and The Schutte Self-Report Emotional Intelligence Test (SSEIT). The finding indicated that there is a significant relationship between adult attachment, anxiety and personality, agreeableness, and neuroticism. The outcome of the study would be an essential finding that would raise awareness on the importance of adult attachment, personality, and emotional intelligence. Knowing our attachment dimension, personality traits, and emotional intelligence would help us develop a working plan to cope with our environment.